2006
DOI: 10.1111/j.1442-2042.2006.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue elasticity imaging for diagnosis of prostate cancer: A preliminary report

Abstract: Background: Elastography is a diagnostic imaging technique that evaluates the hardness of a lesion. It is expected to become a new diagnostic modality for prostate cancer. The aim of this study was to examine the usefulness of elastography in the diagnosis of prostate cancer. Methods: A total of 29 patients with untreated, histologically proven prostate cancer were examined using an elastographic imaging technique. The patient was scanned in the dorsosacral position and the prostate was manually compressed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 12 publications
(24 reference statements)
3
72
0
2
Order By: Relevance
“…One approach that to some extent handles this problem is a display in which each strain image is overlaid on the B-scan as a "colour wash", where colour indicates strain and brightness is partly determined by the ultrasound signal amplitude [7,18]. In so far as ultrasound signal amplitude correlates with the accuracy of strain estimates, this goes some way to indicating the quality of the strain data.…”
Section: Interface Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach that to some extent handles this problem is a display in which each strain image is overlaid on the B-scan as a "colour wash", where colour indicates strain and brightness is partly determined by the ultrasound signal amplitude [7,18]. In so far as ultrasound signal amplitude correlates with the accuracy of strain estimates, this goes some way to indicating the quality of the strain data.…”
Section: Interface Conceptmentioning
confidence: 99%
“…Regarding the colour scheme, our options include the use of a wide range of saturated colours, producing the effect of a contour display (as for example in the blue-cyan-green-yellow-red scale of [7] and [18]), but for the present demonstration we favour a dichromatic scale, which is qualitatively closer to traditional intensity-based displays, and which may avoid distorting the features that are perceived to appear in each image. Aiming for maximum colour variation across our example scale, we use green and magenta at the extremes, varying from strong green (high strain/soft) through grey (medium strain/medium stiffness) to magenta (low strain/stiff).…”
Section: Displaymentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the method used are not described extensively, although they refer to their recent study 7 conducted on pregnant women in the third trimester of pregnancy based on real-time elastography. In this paper 7 , Fuchs and colleagues simply stated that: 'the Hitachi 7500 ultrasound device uses the method designed by Shiin et al allowing for real-time assessment of the tissue elasticity', giving no reference; after searching online we found some studies carried out by Tsuyoshi Shiina, to which we suppose Fuchs et al were referring, that used real-time freehand elasticity imaging 8 . If the authors used this approach, as it seems they did, no clarification is given as to how they propose to standardize the force applied.…”
mentioning
confidence: 99%
“…Ultrasound elastography is a unique method which combines the advantages of DRE and ultrasound for the assessment of the bioelasticity distribution in vivo by displaying strain images of tissues. Studies have shown that elastography improves the diagnostic effectiveness for prostate cancer (PCa) by compensating for the limitations of DRE, such as the lesion depth and the physician's experience (Miyanaga et al, 2006;Belbase et al, 2013). This technique has been applied widely in the diagnosis of many kinds of tumors.…”
Section: Introductionmentioning
confidence: 99%